Post-partum psychiatric disorders - Tuteja, Tanvi Vijay; Niyogi, Geeta Madhav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Post-partum period is demanding period characterized by overwhelming biological, social and emotional changes. It requires significant personal and interpersonal adaptation, especially in case of primigravida. Childbearing from the standpoint of psychological medicine is the most complex event in human experience. Traditionally Inwood has classified post-partum psychiatric disorders (PPPD) as maternity blues, post-partum (postnatal) depression and puerperal psychosis (PP). However the spectrum of postpartum phenomenology is widely characterized by range of emotions from transient mood liability, irritability and weepiness to marked agitation, delusions, confusion and delirium. Untreated post-partum depression can have adverse long term effects. For the mother, the episode can be the precursor of chronic recurrent depression. For her children a mother’s ongoing depression can contribute to emotional, cognitive and interpersonal problems in later life. And therefore a thorough knowledge of the same is important for all obstetrician and gynecologists.